High sensitivity and clonal stability of the genomic fusion as single marker for response monitoring in ETV6-RUNX1-positive acute lymphoblastic leukemia - Hoffmann, Jana; Krumbholz, Manuela; Gutiérrez, Helia Pimentel; Fillies, Marion; Szymansky, Annabell; Bleckmann, Kirsten; zur Stadt, Udo; Köhler, Rolf; Kuiper, Roland P.; Horstmann, Martin; von Stackelberg, Arend; Eckert, Cornelia; et al. (Pediatric Blood & Cancer, 2019)
Background: Assessment of minimal residual disease (MRD) is an integral component for response monitoring and treatment stratification in acute lymphoblastic leukemia (ALL). We aimed to evaluate the genomic ETV6-RUNX1 fusion sites as a single marker for MRD quantification. Procedure: In a representative, uniformly treated cohort of pediatric relapsed ALL patients (n = 52), ETV6-RUNX1 fusion sites were compared to the current gold standard, immunoglobulin/T-cell receptor (Ig/TCR) gene rearrangements. Results: Primer/probe sets designed to ETV6-RUNX1 fusions achieved significantly more frequent a sensitivity and a quantitative range of at least 10 –4 compared to the gold standard with 100% and 73% versus 76% and 47%, respectively. The breakpoint sequence was identical at diagnosis and relapse in all tested cases. There was a high degree of concordance between quantitative MRD results assessed using ETV6-RUNX1 and the highest Ig/TCR marker (Spearman's 0.899, P <.01) with differences >½ log-step in only 6% of patients. A high proportion of ETV6-RUNX1-positive ALL relapses (40%) in our cohort showed a poor response to induction treatment at relapse, and therefore had an indication for hematopoietic stem cell transplantation, demonstrating the need of accurate identification of this subgroup. Conclusions: ETV6-RUNX1 fusion sites are highly sensitive and reliable MRD markers. Our data confirm that they are unaffected by clonal evolution and selection during front-line and second-line chemotherapy in contrast to Ig/TCR rearrangements, which require several markers per patient to compensate for the observed loss of target clones. In future studies, the genomic ETV6-RUNX1 fusion can be used as single MRD marker.
CRIS-Team Scopus Importer:2019-05-17
Keywords: acute lymphoblastic leukemia; fusion gene; genomic breakpoint; minimal residual disease; response monitoring